Experiments Gone Wrong? Lived Experience of Filipino Teachers in Remote Science Education amid COVID-19 Crisis - Cahapay, Michael B.; Labrador, Mark Gil P. (Asian Journal of Science Education, 2021)
The COVID-19 crisis moved teachers to engage in a sort of emergency instructional experiment to redesign how science could and should be taught. The lived experience of the teachers as implementers in the ground can be a source of practical insights in the continuous improvement of remote science education. Thus, the purpose of this phenomenology research is to analyze the lived experience of teachers in remote science education in the wake of continuing COVID-19 crisis. Through online interview procedures, eight purposively sampled secondary science teachers from public schools in Mindanao, Philippines were involved in this study. Using data analysis framework consistent with the descriptive approach in phenomenology, the responses of the participants were examined in stages. The results revealed four themes: (1) presenting difficult concepts in remote science teaching; (2) encountering challenges in the delivery of remote science teaching; (3) adjusting instructional practices in remote science teaching; and (4) drawing types of support to improve remote science teaching. These themes form the phenomenon of remote science education from the perspective of the teachers in the context of a crisis. Several practical recommendations to improve current remote science instruction are discussed at the end of this paper.